Population Prospects and the Determination of a Debt-Sharing Rule between Seceding Regions - Philippe Cattoir; Frédéric Docquier (Institute for the Study of Labor (IZA), 2004)
This paper investigates one of the most important financial issues arising from a secession or a country partitioning namely the sharing of the national public debt. Extending Dr?ze's distributive neutrality condition, we use the generational accounting technique and propose a dynamic debt-sharing criterion which takes into account both the true debt future generations inherit and their contributive capacity. The equivalence with Dr?ze's static rule is only obtained on the balanced growth path, and in the absence of initial regional debt. An application of our criterion to the Belgian case offers striking results.
Keywords: H77; H60; 330; public debt; secession; generational accounting; Öffentliche Schulden; Finanzausgleich; Separatismus; Intergenerative Belastungsrechnung; Schätzung; Belgien